COMPARATIVE ANALYSIS OF ALISHER NAVAI’S MAJALIS UN-NAFAIS AND SADIQI BEG AFSHOR SADIQI’S MAJMA’ AL-KHAVAS - Irgashevıch, Sultanov Tulkın; Umsmanovna, Ruzmanova Rokhıla (International Journal of Psychosocial Rehabilitation, 2020)
Alisher Navai’s contribution to the development of classical literature of the Turkic peoples is remarkable. The best creatures of Uzbek poet who has been honored as Shams ul-millat, alongside the works of the spiritual and spiritual world of humanity such as Jaloliddin Rumi, Hafiz Sherozi, Alighieri Dante, William Shakespeare and Lev Tolstoy.The first tazkira in the Turkic language, Majalis un-Nafais, was created by Alisher Navai in 1491-1498. The Tazkira consists of 8 majlises. There is given information about 459 poets who lived and created in the 15th century. For example, related informations had been given about 46 poets in the first majlis, 91 in the second majlis, 175 in the third majlis, 72 in the fourth majlis, 21 in the fifth majlis, 31 in the sixth majlis, 22 in the seventh majlis and Khusayn Baykara in the eighth majlis.Sadiqi Beg Afshor is a well-known poet, a well-known scientist and miniature artist who lived in Azerbaijan in the second half of the XVI century and early in the seventeenth century. Informations about life and work of the poet came through his divan and tazkira that called Majma’ al-Khavas.Sadiqi wrote the second tazkira in the 1597-1598 years in the Turkic language Majma’ al-Khavas in the style of Majalis un-Nafais by Alisher Navai. It was composed of 8 majma’s.In the Majma’ al- Khavas a detailed information is given about 369 poets who lived and created works in Persian, Tajik and Turkic languages in Iran, Azerbaijan, Central Asia, Turkey, Afghanistan, Pakistan and India during the reign of King Ismael I. For instance, informations had been given about lives and works of 12 poets in the first majma’, 8 poets in the second majma’, 11 poets in the third majma’, 33 poets in the fourth majma’, 15 poets in the fifth majma’, 39 poets in the sixth majma’, 28 poets in the seventh majma’ and 223 poets in the eighth majma’.In this article ideological and artistic comparisons of Alisher Navai’s Majalis un-Nafais and Sadiqi Afshor’s Majma’ al-Khavas has been revealed.